Offshore Technology Conference 1986
DOI: 10.4043/5302-ms
|View full text |Cite
|
Sign up to set email alerts
|

Collapse Analysis Of Framed Offshore Structures

Abstract: The paper presents new approaches for nonlinear system analysis of trusswork platforms. The main idea behind the technique is.to minimize the cost of the nonlinear analysis by reducing the number of parameters and the size of element model. A brief description is given on the theoretical basis of the computer program including the formulation of incremental stiffness with modifications for plastic hinges. Special emphasis is given to the choice of adequate interpolation functions and to the evaluation of nonli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Fig. 7 also compares the results obtained by the present analysis with the experimental results presented by Soreide et al [34]. The three points of the experimental curve that cross the x-axis may be understood as loading/unloading cycles during the experiment.…”
Section: Tubular K -Framementioning
confidence: 69%
See 2 more Smart Citations
“…Fig. 7 also compares the results obtained by the present analysis with the experimental results presented by Soreide et al [34]. The three points of the experimental curve that cross the x-axis may be understood as loading/unloading cycles during the experiment.…”
Section: Tubular K -Framementioning
confidence: 69%
“…It is of particular interest because it includes all the basic difficulties for collapse analysis, such as a sharp nonlinear response with snap-back after the limit load, column buckling, and formation of several plastic hinges. Moreover, experimental results are available, presented by Soreide et al [34].…”
Section: Tubular K -Framementioning
confidence: 95%
See 1 more Smart Citation
“…The collapse analysis for a similar platform was performed by USFOS pushover analysis, as per Soreide et al (1986), and it was found that the minimum RSR was equal to 2.19 at collapse and 1.76 at first failure in the leg joints at −9.0 m elevation below the mean seal level, i.e., an environmental load from the northwest 119% greater than maximum wave height (H max ) combined with wind speed equal to 15.6 m/s. The pushover analysis revealed an RSR equal to 1.13 at first failure due to pile yield for example increasing environmental load 25% greater than maximum wave 7.8 | Case Study: Platform Failure height with the associated wind speed.…”
Section: Structure Assessmentmentioning
confidence: 99%
“…K-frameIn this example, comparison is made between the prediction of ADAPTIC, using the plastic hinge and distributed plasticity approaches, and the analytical and experimental results reported by Soreide et al6 on the K-frame set-up shown in Figure 7. Although Soreide et al did not include any information regarding the level of imperfections, it was found that ADAPTIC provides best comparison with the experimental ultimate capacity if parabolic imperfections of (L/1000) are assumed in the diagonal members.…”
mentioning
confidence: 99%